Temperature and day length drive local adaptation in the Patagonian foundation tree species Nothofagus pumilio - Sekely, Jill; Marchelli, Paula; Arana, María Veronica; Dauphin, Benjamin; Mattera, Maria Gabriela; Pastorino, Mario Juan; Scotti, Ivan; Soliani, Carolina; Heer, Katrin; Opgenoorth, Lars (BioRxiv, 2023)
Climate change alters relationships among environmental conditions and thus has the potential to change the selection pressures acting on adaptive gene variants. Using a landscape genomic approach, we show that the southern beech species Nothofagus pumilio has notable genetic adaptations to climate along its 2000-kilometer-long range in the Andes. We screened 47,336 SNP loci in 1,632 contigs and found that high-latitude sampling sites have lower genetic diversity, likely due to greater impact of glacial oscillations at high latitudes. Using four genome scan methods, we identified 457 outlier SNPs that are either strongly differentiated among subpopulations or associated with environmental covariates related to temperature, day length, and precipitation. Temperature and day length parameters were associated with notably more outliers than precipitation (n = 133, 113, and 61 outliers, respectively), and almost half of all annotated outliers were related to stress response (n=38, 21%) or catabolism-metabolism (n=43, 24%). Our findings suggest that Nothofagus pumilio is an ideal Andean model of genetic adaptation to climate change because it is locally adapted to extant climate conditions, and shifting patterns among environmental parameters may be detrimental to its future survival and adaptation potential.